Interpretation of the temperature-dependent color of blue copper protein mutants - Comba, Peter; Müller, Vera; Remenyi, Rainer (Journal of inorganic biochemistry, 2004)
The electronic absorption spectrum of the mutant of the blue copper protein amicyanin with a pseudoazurin loop (AmiPse) shows a remarkable temperature dependence. The absorption band at ≈460 nm increases at low temperature while the transition at ≈600 nm is not much affected by a variation of the temperature. An approximate density functional theory (DFT) study of the active site model [CuII(imidazole)2(SCH3)(S(CH3)2)]+ (protein backbone and solvation neglected) leads to two local minimum structures (axial and rhomb) which both have a geometry close to that typical for blue copper proteins. One (rhomb) has two structurally different histidine donors, and this geometry is also found in most experimental type 1 structures. The two forms axial and rhomb are distortional isomers and are energetically almost degenerate. The temperature dependence of the spectrum of AmiPse is interpreted with a temperature-dependent change of the relative population of the two local minimum structures with slightly different energy. The 460 nm transition is believed to be due to preferential population of the structure rhomb; this is in agreement with the published assignment of the high energy transition, based on thorough spectroscopic and computational studies. Consequences of a perturbation of the “gas phase” structures axial and rhomb by the protein and solvation are also discussed on the basis of published, experimentally observed structures and spectroscopic data.